Elastic Recovery Properties of Alginate Impression Materials Based on Red Algae Kappaphycus alvarezii - Indahyani, Didin Erma; Barid, Izzata; Nafisah, Nafisah; Praharani, Depi; Sumono, Agus; Probosari, Niken; Sulistiyani, Sulistiyani (UI Scholars Hub, 2023)
Alginate impression materials in dentistry are used to form details of the oral cavity organs. The alginate content in the impression material functions to form a gel. One source of alginate is algae. Objective: This study aims to determine the recovery elasticity and setting time of alginate impression materials made from red algae K. alvarezii. Methods: The sodium alginate in the composition of this alginate impression material was extracted from red algae K. alvarezii. The alginate impression material was tested for setting time and recovery elasticity and compared with commercial impression material (Hygedent®). Results: The elastic recovery of red algae sodium alginate impression materials was 97.43% which was not significantly different from the commercial impression materials (98.42%). These results showed that this alginate impression material has the same properties as commercial impression materials. In the setting time test, the the red algal alginate impression material was much longer than the commercial impression material, 1.39 m and 3.30 m respectively. Conclusion: It was concluded that the alginate impression material from the red algae K. alvarezii had a long setting time. At the same time, the recovery of elasticity did not differ from that of commercially available alginate impression materials.